MIAVOLT: Pembuatan Dye-Sensitized Solar Cell Berbasis Ekstrak Miana (Coleus scutellarioides L.) dan Klorofil Alfalfa (Medicago sativa L.) sebagai Energi Terbarukan di Daerah Terpencil - Khalisha, Naura; Dyah Athafatin Nafisah; Yuni Hidayani; Susanti Rahayu (SMA Trensains Muhammadiyah Sragen, 2025)
The availability of electricity significantly impacts the quality of life in society. The absence of electricity in several remote areas can limit access to essential facilities and affect the well-being of residents. One effort to expand electricity access is through the utilization of alternative energy sources. However, using conventional technology to generate electricity in remote areas is often challenging due to geographical conditions and infrastructure limitations. This study aims to develop a Dye-Sensitized Solar Cell (DSSC) based on miana extract and chlorophyll from alfalfa leaves as an alternative for renewable energy production in remote areas. The research adopts a descriptive method with a quantitative approach. Data collection is conducted through observation and literature review. The indicators of product effectiveness include: 1) open-circuit voltage test; 2) short-circuit current test; 3) optimum voltage test; 4) optimum current test; 5) maximum power test; 6) fill factor test; 7) energy conversion efficiency test. The data analysis technique used is descriptive quantitative. This study concludes that the development of DSSC from natural materials not only supports the provision of alternative energy for remote areas but also reduces dependency on fossil fuels, which are limited and have negative environmental impacts. Natural material-based DSSC provides a sustainable solution for affordable and eco-friendly electricity in areas with limited electricity access.